Design and Control of the Manipulator of Magnetic Surgical Forceps with Cable Transmission - Jingwu Li; Zhijun Sun (Micromachines)
Magnetically actuated medical robots have attracted growing research interest because magnetic force can transmit power in a non-contact manner to fix magnetic surgical instruments onto the inner wall of the abdominal cavity. In this paper, we present magnetic and cable-driven surgical forceps with cable transmission. The design achieves significant diameter reduction in the manipulator by separating the power sources (micro-motors) from the manipulator through cable transmission, consequently improving surgical maneuverability. The manipulator adopting cable transmission mechanism has the problem of joint motion coupling. Additionally, due to the compact space within the magnetic surgical forceps, it is difficult to install pre-tightening or decoupling mechanisms. To address these technical challenges, we designed a pair of miniature pre-tensioning buckles for connecting and pre-tensioning the driving cables. A mathematical model was established to characterize the length changes of the coupled joint-driving cables with the angles of moving joints and was integrated into the control program of the manipulator. Joint motion decoupling was achieved through real-time compensation of the length changes of the coupled joint-driving cables. The decoupling and control effects of the manipulator have been verified experimentally. While one joint moves, the angle changes of the coupled joints are within 2°.